High-fat diet causes undesirable bone regeneration by altering the bone marrow environment in rats - Cai, Feiyu; Yusufu, Aihemaitijiang; Liu, Kai; Chen, Wenjiao; Zhao, Ruomei; Liu, Yanshi; Liu, Yi (Frontiers in Endocrinology, 2023)
Objective Diet structure has changed greatly over the last few decades, and high-calorie diets have become an integral part of people's daily diet, as well as the important cause of obesity in society. Several organ systems, including the skeletal system, are seriously affected by high-fat-diets (HFD) in the world. There is, however, still a lack of knowledge about the effects of HFD on bone regeneration and the possible mechanisms involved. In this study, the difference in bone regeneration between rats under HFD and low-fat-diets (LFD) was evaluated by monitoring the process of bone regeneration in distraction osteogenesis (DO) model animals, as well as the possible mechanisms. Methods A total of 40 Sprague Dawley (SD) rats (5 weeks old) were randomly divided into HFD group (n=20) and LFD group (n=20). Except for feeding methods, there were no differences between the two groups in terms of treatment conditions. All animals received the DO surgery eight weeks after starting to feed. After a delay of 5 days (latency phase), the active lengthening phase was performed for 10 days (0.25 mm/12 h), and the consolidation phase followed for 42 days. An observational study of bone included radioscopy (once a week), micro-computed tomography (CT), general morphology, biomechanics, histomorphometry, and immunohistochemistry. Result The results showed that HFD group had a higher body weight than LFD group after 8, 14, and 16 weeks of feeding. Furthermore, at the final observation, there were statistically significant differences between LFD group and HFD group in terms of total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), and high-density lipoprotein (HDL) levels. Additionally, observations on bone regeneration showed a slower regeneration and a lower biomechanical strength in HFD group than LFD group, based on radiography, micro-CT, general morphology, biomechanics, histomorphometry, and immunohistochemistry. Conclusion In this study, HFD resulted in elevated blood lipids, increased adipose differentiation at the bone marrow level, and delayed bone regeneration. The pieces of evidence are beneficial to better understand the association between diet and bone regeneration and to adjust the diet optimally for fracture patients.